Data book on hydrocarbons : Application to process engineering - Maxwell, J. B. (The Esso series, 1968)
Physical constants - Characteristics of petroleum fractions - Molecular weight - Vapor pressure - Fugacity - Critical properties - Thermal properties - Density - Viscosity - Combustion - Flow of fluids - Flow of heat - Equilibrium flash vaporization - Fractionating towers - Conversion factors.